Implementation of modified SARSA learning technique in EMCAP - Ganesha, D.; Venkatamuni, Vijayakumar Maragal (International Journal of Engineering and Technology, 2017)
This research work presents analysis of Modified Sarsa learning algorithm. Modified Sarsa algorithm.Â State-Action-Reward-State-Action (SARSA) is an technique for learning a Markov decision process (MDP) strategy, used in for reinforcement learning int the field of artificial intelligence (AI) and machine learning (ML). The Modified SARSA Algorithm makes better actions to get better rewards.Â Experiment are conducted to evaluate the performace for each agent individually. For result comparison among different agent, the same statistics were collected. This work considered varied kind of agents in different level of architecture for experiment analysis. The Fungus world testbed has been considered for experiment which is has been implemented using SwI-Prolog 5.4.6. The fixed obstructs tend to be more versatile, to make a location that is specific to Fungus world testbed environment. The various parameters are introduced in an environment to test a agentâ€™s performance. This modifiedÂ Â SARSA learning algorithm canÂ Â be more suitable in EMCAP architecture.Â The experiments are conducted the modifiedÂ Â SARSA Learning system getsÂ Â more rewards compare to existingÂ SARSA algorithm.